Immunohistochemical and molecular analysis of PI3K/AKT/mTOR pathway in esophageal carcinoma. Issue 8 (27th April 2015) - Tasioudi, Konstantia E.; Sakellariou, Stratigoula; Levidou, Georgia; Theodorou, Dimitrios; Michalopoulos, Nikolaos V.; Patsouris, Efstratios; Korkolopoulou, Penelope; Saetta, Angelica A.
<x xml:space="preserve">Abstract</x> Among the numerous signaling pathways involved in tumorigenesis, PI3K‐AKT‐mTOR is a key one that regulates diverse cellular functions. However, its prognostic value in esophageal carcinoma remains unclear. In our study, we examined the immunohistochemical expression of phosphorylated (p‐) AKT, mTOR, p70S6K and 4E‐BP1 along with the mutational status of PIK3CA and AKT1 genes by High Resolution Melting Analysis and Pyrosequencing in 44 esophageal carcinomas. The results were correlated with the clinicopathological characteristics of the patients in an effort to define their possible prognostic significance. Total p‐mTOR cytoplasmic expression, assessed in 10 random areas, was positively correlated with tumor stage (Kruskal–Wallis ANOVA, I/II vs III/IV, p = 0.0500). Μoreover, maximum p‐mTOR cytoplasmic immunoexpression, estimated in hot spot areas, was positively associated with tumor grade (Mann–Whitney U test, I/II vs III, p = 0.0565). Interestingly, p‐4E‐BP1 immunoreactivity was negatively correlated with tumor histological grade (Mann–Whitney U test, I/II vs III, p = 0.0427). No mutation was observed in exons 9 and 20 of PIK3CA gene and in exon 4 of AKT1 gene. In conclusion, our findings depict the presence of activated PI3K/AKT/mTOR pathway in esophageal cancer bringing forward p‐mTOR and p‐4E‐BP1 for their potential role in esophageal carcinogenesis. Additional studies are warranted to validate our findings.